2010
DOI: 10.1074/jbc.m110.146076
|View full text |Cite
|
Sign up to set email alerts
|

Heme Amplifies the Innate Immune Response to Microbial Molecules through Spleen Tyrosine Kinase (Syk)-dependent Reactive Oxygen Species Generation*

Abstract: Infectious diseases that cause hemolysis are among the most threatening human diseases, because of severity and/or global distribution. In these conditions, hemeproteins and heme are released, but whether heme affects the inflammatory response to microorganism molecules remains to be characterized. Here, we show that heme increased the lethality and cytokine secretion induced by LPS in vivo and enhanced the secretion of cytokines by macrophages stimulated with various agonists of innate immune receptors. Activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
97
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 37 publications
3
97
1
1
Order By: Relevance
“…S1 A and B). We have previously shown that the synergistic effect of heme on cytokine production triggered by microbial molecules only occurs in the presence of serum (24). Thus, we tested the requirement of serum on heme-induced IL-1β processing.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…S1 A and B). We have previously shown that the synergistic effect of heme on cytokine production triggered by microbial molecules only occurs in the presence of serum (24). Thus, we tested the requirement of serum on heme-induced IL-1β processing.…”
Section: Resultsmentioning
confidence: 99%
“…Heme is a potent inducer of ROS production, activating different sources of ROS generation in macrophages (19,24). Recent studies indicate an essential role of mitochondrial ROS (mtROS) on NLRP3 activation induced by several stimuli (48,49).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations